2018
DOI: 10.1021/acscatal.7b03467
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Reactions of O2 and CO2 on Ionically Conducting Catalyst

Abstract: The presence of CO2, an unavoidable component in air and fuel environments, is known to cause severe performance degradation in oxide catalysts. Understanding the interactions between O2, CO2, and ion-conducting oxides is critical to developing energy-conversion devices. Here, surface reaction kinetics of Ba0.5Sr0.5Co0.8Fe0.2O3‑δ (BSCF) with the presence of both O2 and CO2 is determined using gas-phase isotope exchange. BSCF actively reacts with CO2, and the incorporation of oxygen from CO2 to the lattice of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Apparently, the presence of CO 2 markedly inhibits the desorption of oxygen for both SFS05 and SFS20, with the reduction being more pronounced for the former. These findings are in good agreement with recent results of isotopic exchange experiments, which showed that CO 2 preferably adsorbs on BSCF perovskite surface and inhibits oxygen surface exchange.…”
Section: Resultssupporting
confidence: 93%
“…Apparently, the presence of CO 2 markedly inhibits the desorption of oxygen for both SFS05 and SFS20, with the reduction being more pronounced for the former. These findings are in good agreement with recent results of isotopic exchange experiments, which showed that CO 2 preferably adsorbs on BSCF perovskite surface and inhibits oxygen surface exchange.…”
Section: Resultssupporting
confidence: 93%
“…This CO 2 exchange peak intensity increases as the CO 2 concentration increases, suggesting that CO 2 exchanges more readily at this temperature. Compared to BSCF, the state of the art cathode, LSCF shows a lower CO 2 reactivity, 50 probably because of different interactions between CO 2 and Ba/La in A site of ABO 3 perovskite.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…Samples are exposed to a variety of gases while heating up at a fixed ramp rate, and the different exchange products are monitored, providing information on heteroexchange between 18 O 2 gas and solid oxygen in the material, along with homoexchange between 18 O 2 and C 16 O 2 . The other technique is isotope-saturated TPX (ISTPX), where sample powders are pretreated with 18 O to utilize the powder as the isotope source (Figure b). The interactions of various gas components such as C 16 O 2 , and 16 O 2 , with the 18 O labeled solid material as a function of temperature, can then be visualized. The combination of these two techniques provides a clearer picture of the multiple gas–gas and gas–solid reactions.…”
Section: Co2–o2 Isotope Exchange Mechanismmentioning
confidence: 99%
“…Although the CO 2 concentration is very low, it is still essential to explore the ability of the cathode to resist CO 2 poisoning for the long-term stable operation of SOFCs. Yan et al found that the performance of the BSCF cathode was adversely affected when the cathode gas contained CO 2 even if its content was very low (0.85 vol %), especially at temperatures below 600 °C. By using the in situ gas-phase isotopic oxygen exchange technique, Huang et al also demonstrated that BSCF can react with CO 2 . The production of carbonate (e.g., Sr 0.6 Ba 0.4 CO 3 ) decreased the rate of oxygen surface exchange, but the surface kinetics and cell performance can be recovered by recalcining the deactivated electrode in highly oxidizing atmosphere above 800 °C. , Much effort has been devoted to addressing the problem of CO 2 poisoning in BSCF.…”
Section: Energy Storage and Conversion Applicationsmentioning
confidence: 99%
“…103−105 By using the in situ gasphase isotopic oxygen exchange technique, Huang et al also demonstrated that BSCF can react with CO 2 . 106 The production of carbonate (e.g., Sr 0.6 Ba 0.4 CO 3 ) decreased the rate of oxygen surface exchange, but the surface kinetics and cell performance can be recovered by recalcining the deactivated electrode in highly oxidizing atmosphere above 800 °C. 103,107 Much effort has been devoted to addressing the problem of CO 2 poisoning in BSCF.…”
Section: Energy Storage and Conversion Applicationsmentioning
confidence: 99%